Evaluation Of Leprosy Management Program Implementation In Karang Penang Health Center, Sampang District, Madura - Reny Nugraheni; Meira Kusuma Wardani (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The sample in this study was leprosy surveillance data, while the informants consisted by two key informants and four main informants. Data processing in this research is quantitative data processing. The results showed that for ‘aspects of health status produced’ there was only one aspect which has fulfilled national standard, namely cure rate (MB and PB); ‘aspects of service quality that have been implemented’ have been achieved; ‘aspects of quantity of services provided’ (ICF activities, drug administration according to dosage, and home visits), which are not optimal because this program runs only for affordable areas and there are still limited resources and facilities that do not support; ‘aspects of community attitudes’ that strongly support this program to be implemented, but community stigma is still low; ‘aspects of available resources’ have not been good due to limited human resources and facilities; and ‘aspects of costs source’ used are from the government